The role of Shh signalling pathway in central nervous system development and related diseases - Li, Xiaoying; Li, Yunxiao; Li, Shuanqing; Li, Han; Yang, Ciqing; Lin, Juntang (Cell biochemistry and function, 2021)
Sonic hedgehog (Shh) plays important roles in developmental of vertebrate animal central nervous system (CNS), and Gli is its downstream signal molecule. Shh signalling is essential for pattern formation, cell‐fate specification, axon guidance, proliferation, survival and differentiation of neurons in CNS development. The abnormal signalling pathway of Shh leads to the occurrence of many nervous system diseases. The mechanism of Shh signalling is complex and remains incompletely understood. Nevertheless, studies have revealed that Shh signalling pathway is classified into canonical and non‐canonical pathways. Here we review the role of the Shh signalling pathway and its impact in CNS development and related diseases. Specifically, we discuss the role of Shh in the spinal cord and brain development, cell differentiation and proliferation in CNS and related diseases such as brain tumour, Parkinson's diseases, epilepsy, autism, depression and traumatic brain injury. We also highlight future directions of research that could help to clarify the mechanisms and consequences of Shh signalling in the process of CNS development and related diseases. Significance of the study This review summarized the role of Shh signalling pathway in CNS development and related diseases such as brain tumour, Parkinson's diseases, epilepsy, autism, depression and traumatic brain injury. It also presented the author's opinions on the future research direction of Shh signalling pathway.